(untitled) (Al-Qamar, 2021)
Allah Almighty has sent His messengers for the guidance of human being who announced the Oneness of Allah in there concerned ages. They made aware the human being of their creator. The series of Anbiyā and the Rasools started from Adam and ended with Prophet Muhammad (ﷺ). After prophet Muhammad the responsibility of preaching the shifted on the shoulders of Sahaba, Tāb̒īns and Tab̒ Tāb̒īns. After them Sufis fulfilled the responsibility of preaching of Islam. They performed their duties efficiently and preached Islam to all corners of the world. There are four Silsilas of Sufis which are:(1) :Chishtia, (2) :Qādria, (3):Naqshbandi, (4)Sohervardia. Chishtia is divided into two: Chishtia Nizāmia and Chishtia Sābria. The Sufis of Chishtia Silsila presented themselves in front of people and to attain the love of Allah and the Rasool. They had experienced the difficulties and hardships that other Sufis did not face. They are torch bearer. They spent their lives according to the teaching of the Prophet (ﷺ). If the descendent of the Khanqah’s follow the teaching of the Sufis the people will able to understand the real concept of Tasawwuf and misconceptions about Sufis will vanish away.